1990
DOI: 10.1113/jphysiol.1990.sp018029
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of mucus secretion by cells isolated from the rat gastric mucosa.

Abstract: SUMMARY1. A suspension of cells, containing about 30 % mucous cells, was isolated from the rat fundic mucosa, and was pre-incubated with D-[6-311]glucosamine. 3H-labelled material subsequently released into the medium was separated by Fast Protein Liquid Chromatography on a Superose 6 column.2. A sharp peak of labelled high molecular weight material eluted from the column close to the void volume. This material was identified as mucous glycoprotein by its similar chromatographic behaviour to partially purified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…This finding supports previous results obtained using isolated rat cells [2]. In contrast, EGF has been shown to stimulate synthesis and secretion of mucus glycoproteins in human gastric mucosa [14] and primary culture of rabbit mucosal cells [13].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This finding supports previous results obtained using isolated rat cells [2]. In contrast, EGF has been shown to stimulate synthesis and secretion of mucus glycoproteins in human gastric mucosa [14] and primary culture of rabbit mucosal cells [13].…”
Section: Discussionsupporting
confidence: 82%
“…Even in in vitro studies, the effects of the major acid secretagogues remain controver sial [2][3][4][15][16][17]. Although the reason is unclear, these discrepancies may reflect species differences or experi mental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, EP4-mediated increases in mucus secretion and intestinal fluid secretion have been found to contribute to the process of intestinal ulcer healing (Kunikata et al, 2002). It has also been reported that cAMP contributes to gastrointestinal mucin secretion, including its principal functional component, mucus glycoprotein (Keates and Hanson, 1990;Słomiany and Słomiany, 2005). Słomiany and Słomiany (2005) demonstrated that b-adrenergic GPCR activation and subsequent AC activation triggered mucin secretion via both the PKA and PI3K pathways.…”
Section: Other Immune Cellsmentioning
confidence: 99%
“…Therefore, in the ACh response, this positive feedback mechanism could effectively be activated. This may explain the former report that ACh is much more effective than His in mucin secretion and cell proliferation (Keates and Hanson, 1990;McCool et al, 1990).…”
Section: Physiological Functional Role Of the Caz+-activated K + Chanmentioning
confidence: 80%